2012
DOI: 10.1111/j.1468-0459.2012.00460.x
|View full text |Cite
|
Sign up to set email alerts
|

Lichenometric ages of the little ice age moraines on king george island and of the last volcanic activity on penguin island (west antarctica)

Abstract: The recently observed recession of glaciers on King George Island is associated with decades of climate warming in the Antarctic Peninsula region. However, with only 60 years of glaciological observations in the study area ages of the oldest moraines are still uncertain. The goal of the study was to estimate ages of lichen colonization on the oldest moraines of the Ecology and White Eagle Glaciers on King George Island and on the Principal Cone of Penguin Island volcano. The first lichenometric studies on thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 64 publications
0
15
0
1
Order By: Relevance
“…Obtained lichenometric ages (Table 1) are older then those of Evans et at. (1999) who used linear growth rate of 0.8 mm year −1 and exceptionally short colonisation lag time which is contradictory to numerous liche− nometrical studies (Gordon and Sharp 1983;Bradwell 2001;Angiel and Dąbski 2012). Evant et al 1999 concluded that such an approach produces underestimated dates for certain moraines of neighbouring Heinabergsjökull, which apparently also applies to younger moraines of Skálafellsjökull.…”
Section: Resultsmentioning
confidence: 82%
“…Obtained lichenometric ages (Table 1) are older then those of Evans et at. (1999) who used linear growth rate of 0.8 mm year −1 and exceptionally short colonisation lag time which is contradictory to numerous liche− nometrical studies (Gordon and Sharp 1983;Bradwell 2001;Angiel and Dąbski 2012). Evant et al 1999 concluded that such an approach produces underestimated dates for certain moraines of neighbouring Heinabergsjökull, which apparently also applies to younger moraines of Skálafellsjökull.…”
Section: Resultsmentioning
confidence: 82%
“…Larger land-terminating glaciers in ASPA-128 (for example, Sphinx and Tower glaciers) with feeding areas below 300 m a.s.l., also experienced significant area loss ( Figure 6). Correspondingly large decreases in the ice cover were observed 30 km to the east in ASPA-151 (for example, Reference [6] for glaciers fed from the Krakow Icefield (300 m a.s.l.)). As simulated by Rückamp et al [8], the small independent ice cap on Bellingshausen Dome (summit at 270 m a.s.l., eastern King George Island) will disappear within the next 300 years under the current climate conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The first field studies of glaciers in Admiralty Bay were conducted in the 1950s and reported a general reduction in ice extent [7]. Since the 1950s, an increased glacier retreat has been reported on King George Island by numerous studies [6,[8][9][10][11][12]]. An increase in surface temperature was also observed over the past several years.…”
Section: Characterization Of the Research Areamentioning
confidence: 93%
See 1 more Smart Citation
“…The mean annual air temperature (MAAT) calculated for joined periods [2006][2007] and 2012 is −1.5 • C [28]. An increase in MAAT by 1.2 • C occurred for the period of 1948-2011 on KGI [29], which resulted in retreat of local glaciers [16,30,31]. However, a set of end moraines developed at the contemporary margin of Baranowski Glacier and recent deceleration of glacial surface lowering [18] can be attributed to a slightly negative temperature trend observed since the beginning of the twenty-first century [32].…”
Section: Of 22mentioning
confidence: 99%